A SYSTEMATIC LITERATURE REVIEW ON RISK MANAGEMENT FOR INFORMATION TECHNOLOGY - Dr Anil Kumar Mahra (International Journal of Advanced Science and Technology, 2019)
In today’s information technology era, several organizations use automated digital technology andinformation technology application to develop their business for better maintenance of their operations.The information technology risk management plays a critical role in defending an organization’svaluable data and information assets. The main aim of information technology risk management is toprotect the digital system from IT-related risk. An effective and efficient risk management process is asignificant part of an efficacious information technology security program. A good IT risk managementapproachaim should be to protect the organization and its resources to perform their operation, not justits digital assets. Consequently, the risk management process should not be treated primarily as atechnical function carried out by the IT experts who operate and manage the IT system, but as anessential management function of the organization. The purpose of this paper is to explore the field of riskmanagement for information technology. The risks of information assets have complex nature; themanagement of risk of information security is addressed by different approaches. The paper provides asystematic literature review on risk management for information technology. To accomplish this purposewe conducted a Systematic Review of the literature in the popularliterature databases. It determined thatthere are several studies about the methods, exist different approaches about the risk analysis.